Prolactin-Releasing Peptide: Physiological and Pharmacological Properties - Pražienková, Veronika; Popelová, Andrea; Kuneš, Jaroslav; Maletínská, Lenka (International journal of molecular sciences, 2019)
Prolactin-releasing peptide (PrRP) belongs to the large RF-amide neuropeptide family with a conserved Arg-Phe-amide motif at the C-terminus. PrRP plays a main role in the regulation of food intake and energy expenditure. This review focuses not only on the physiological functions of PrRP, but also on its pharmacological properties and the actions of its G-protein coupled receptor, GPR10. Special attention is paid to structure-activity relationship studies on PrRP and its analogs as well as to their effect on different physiological functions, mainly their anorexigenic and neuroprotective features and the regulation of the cardiovascular system, pain, and stress. Additionally, the therapeutic potential of this peptide and its analogs is explored.
Keywords: energetický metabolismus; energy expenditure; Receptors, G-Protein-Coupled; neuroprotektivní látky; signaling; přijímání potravy; Structure-Activity Relationship; prolactin-releasing peptide; Neurodegenerative Diseases; signální transdukce; Neuroprotective Agents; Eating; Signal Transduction; Prolactin-Releasing Hormone; vztahy mezi strukturou a aktivitou; neuroprotection; neurodegenerativní nemoci; RF-amide peptides; Animals; lidé; Energy Metabolism; Humans; GPR10; zvířata; receptory spřažené s G-proteiny; hormon uvolňující prolaktin; food intake regulation